Application to Determination of Scholarship Worthiness Using Simple Multi Attribute Rating Technique and Merkle Hellman Method - Nofriansyah, Dicky (Universitas Dharma Wacana, 2017)
This research was focused on explaining how the concept of simple multi attribute rating technique method in a decision support system based on desktop programming to solve multi-criteria selection problem, especially Scholarship. The Merkle Hellman method is used for securing the results of choices made by the Smart process. The determination of PPA and BBP-PPA scholarship recipients on STMIK Triguna Dharma becomes a problem because it takes a long time in determining the decision. By adopting the SMART method, the application can make decisions quickly and precisely. The expected result of this research is the application can facilitate in overcoming the problems that occur concerning the determination of PPA and BBP-PPA scholarship recipients as well as assisting Student Affairs STMIK Triguna Dharma in making decisions quickly and accurately